Special Primary School Complex in the United Kingdom Booker Park - Robinson, Mark (PEB Exchange, Programme on Educational Building, 2008)
Booker Park School is a new complex for pre-primary children and primary pupils with a range of behavioural and learning difficulties. To respond to the pupils' varied needs, the school facilities offer a high degree of flexibility and a quality environment for learning